Comprehension of rapidly transforming landscapes of Central and Eastern Europe in the 20th century - Mimi Urbanc; Anu Printsmann; Hannes Palang; Ewa Skowronek; Witold Woloszyn; Éva Konkoly Gyuró (Acta Geographica Slovenica, 2004)
The article presents landscapes as natural, historical, cultural, social and political phenom-ena, and above all as a meaningful part of the environment. We will argue – by giving a contextual framework of landscape changes followed by four case studies from Central and Eastern Europe – that comprehen-sion of landscapes has declined in the 20thcentury. Along with urbanization, globalization and other societal processes rapidly varying socio-economic formations have caused alienation: changes in power result in changes in a society's values and thus some landscape elements are disintegrating, fading or disappear-ing and, as a result, these landscapes are taking on new, altered or modified appearances, functions and meanings. Every change in landscape needs some time to become accepted but if this re-coding of what is regarded as valuable is constantly changing, people become confused, with resultant physical conse-quences: land abandonment; illegal dumping; ill fitting infrastructures; inappropriate housing developments; etc. The main question is whether modern development, e.g. tourism, enhances the relationship between people and the landscape.